Psikoterapi Islam Bagi Seseorang Yang Jatuh Cinta Dalam Perspektif Hadīṡ (Kajian Ma’ānil Hadīṡ) - Rahim, Sofi Nurul (UIN Sumatera Utara Medan, 2023)
This study aims to find out how to actually understand ḥadīṡ about Islamic psychotherapy for someone who falls when applied in life. The benefits and usefulness of this research are to add to the treasures and provide an understanding that often occurs in understanding the matter of falling in love. This type of research is classified as library research, namely research that examines literature related to discussions related to love for the opposite sex. This study uses takhrij ḥadīṡ and ma'anil ḥadīṡ which then in understanding it uses the Yusuf al-Qaraḍawi approach in understanding ḥadīṡ, including: Understanding the Sunnah according to the instructions of the Al-Qur'ān, Collecting ḥadīṡ- Thematic ḥadīṡ, Combining and reviewing ḥadīṡ-ḥadīṡ which seem contradictory, Understanding ḥadīṡ by looking at the background, situation (asbab al-Wurūd) and its purpose, Distinguishing between fixed means and changing means, Distinguishing between meaningful expressions that real and majāz in understanding ḥadīṡ, Distinguishing between the realms of the unseen and the real world, Confirming the meaning and connotation of the words in ḥadīṡ. So that there is no rigidity in religion which affects all aspects of life. As a conclusion from the research conducted based on the understanding of asbab al-Wurūd, Takhrij, ma'anil ḥadīṡ and other syara' provisions, namely: 1. The quality of the sanad is marfu', including the ḥadīṡ masyhur who is ṣaḥīḥ, 2. The concept the love taught by the three ḥadīṡ forbids us from expressing love in the wrong way so that it can lead us to disobedience 3. The solution given for people who fall in love is to marry, love naturally and on the basis of faith in Allāh and His Messenger.